Clinical Utility of Intraoperative Parathyroid Hormone Measurement in Children and Adolescents Undergoing Total Thyroidectomy - Tsai, Steven D.; Mostoufi-Moab, Sogol; Bauer, Samantha; Kazahaya, Ken; Hawkes, Colin P.; Adzick, N. Scott; Bauer, Andrew J. (Frontiers in Endocrinology, 2019)
Background Hypoparathyroidism is one of the most common complications for patients undergoing total thyroidectomy. Our study’s primary objective was to assess if intraoperative PTH levels correlate with parathyroid gland function recovery time in pediatric patients following total thyroidectomy. Methods Retrospective review of pediatric patients who underwent thyroid surgery at CHOP for demographics and laboratory test values (calcium, phosphorus and parathyroid hormone). We defined Time of Recovery (TOR) as the time difference from first intra-operative parathyroid hormone level (ioPTH) timepoint until normalization of PTH (>10 pg/mL) post-thyroidectomy. Calcium and vitamin D supplements were weaned following normalization of calcium and phosphorous levels postoperatively. Patients were excluded if they lacked three intraoperative PTH timepoints or were missing postoperative follow-up PTH data. Results 65 patients (54 female), median age 15 (range 5-23 years), underwent thyroid surgery and met study inclusion criteria. The correlations of 2nd and 3rd ioPTHs with TOR were statistically significant (p < 0.05): the lower the ioPTH, the greater the recovery time. Stratifying patients into high-risk (2nd ioPTH  10 pg/mL), moderate-risk (2nd ioPTH between 10 and 20 pg/mL), and low-risk (2nd ioPTH  20 pg/mL) tertiles, the TOR decreased by orders of magnitudes from an average of 43.13 ± 76.00 to 6.10 ± 17.44 to 1.85 ± 6.20 days. These differences were statistically significant (p < 0.05). Conclusions Our study results confirm the usefulness of intraoperative PTH levels to predict pediatric patient recovery post-surgery and provides useful anticipatory guidance to optimize timing and frequency of postoperative laboratory surveillance.